Gaya Kepemimpinan Dalam Meningkatkan Kinerja Karyawan Pada PT. Bank Mandiri (Persero) Micro Banking Cluster Jember - masrohatin, siti; Isabella, Al Fitri Ummi; Salsabilla, Yasmin huronia (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2023)
Leadership style is the norm of behavior used by a person when he tries to influence the behavior of others. The leadership style will be suitable if the company's goals have been communicated and employees have accepted them. A leader must apply a leadership style to manage employees because it will greatly affect the success of the organization in achieving its goals. Leaders should listen to ideas from employees before making decisions. The appropriate leadership style will motivate a person to achieve. Success or failure in employee performance can be influenced by the manager's leadership style. This study aims to describe the leadership style in improving employee performance at PT Bank Mandiri (Persero) Micro Banking Cluster Jember 1. This study uses the observation method, namely going directly to Bank Mandiri micro banking cluster Jember 1 to obtain accurate information. Data collection techniques using data triangulation, namely observation, interviews and documentation. The purpose of this study was to determine how the leadership style in improving employee performance at PT Bank Mandiri (Persero) Micro Banking Cluster Jember